IMPLEMENTASI PROGRAM INOVASI DIGITAL SISABAR (SISTEM INFORMASI SAYANG BARUDAK) SEBAGAI PLATFORM PENGADUAN PERLINDUNGAN ANAK DI KABUPATEN TANGERANG - Sierfi Rahayu; Kiki Faisal (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
In implementing child protection, violence against children is still the most serious and disturbing problem in society. Law Number 35 of 2014 concerning child protection. The legal basis that becomes a reference in protecting children from cases of violence. The aim of this research is to determine the implementation of the SISABAR digital innovation program. This research uses the Grindle implementation model. This research method is descriptive qualitative. The results of the research are that the implementation of the SISABAR digital innovation program is optimal, the two dimensions of the Grindle model, namely the content of policy dimension, show that SISABAR innovation is a strategy for the Tangerang district government in the midst of the Covid 19 pandemic in 2020. The desired benefits from implementing the SISABAR innovation program can reduce the number of cases of violence against children because they are digital based. Involving several OPDs such as the Education Service, Social Service, Health Service, Police and Clinical Psychology. However, the context of implementation dimension needs to be optimized, as in the sub-dimensions of compliance and responsiveness of the target group. Keywords; Child Protection, Implementation, SISABAR